2019
DOI: 10.1111/bjd.18088
|View full text |Cite
|
Sign up to set email alerts
|

Changing our microbiome: probiotics in dermatology

Abstract: Summary Background Commensal bacteria are a major factor in human health and disease pathogenesis. Interest has recently expanded beyond the gastrointestinal microbiome to include the skin microbiome and its impact on various skin diseases. Objectives Here we present current data reviewing the role of the microbiome in dermatology, considering both the gut and skin microflora. Our objective was to evaluate whether the clinical data support the utility of oral and topical probiotics for certain dermatological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 97 publications
(201 reference statements)
0
75
0
5
Order By: Relevance
“…The results of a recent meta-analysis from controlled in vivo studies testing the efficacy of probiotics for skin lesions in animal models strongly support that topical probiotic administration is an effective pharmacological treatment for cutaneous wounds [43]. The new perspective and therapeutic potential of beneficial probiotic species as an alternative and safe approach for the treatment of patients affected by cutaneous disorders, including non-healing wounds, has been recently reviewed [7,17]. Our data extend the spectrum of the mechanisms underlying the effects of specific probiotics on the re-epithelialization process and may further justify their use in the topical treatment of skin wounds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of a recent meta-analysis from controlled in vivo studies testing the efficacy of probiotics for skin lesions in animal models strongly support that topical probiotic administration is an effective pharmacological treatment for cutaneous wounds [43]. The new perspective and therapeutic potential of beneficial probiotic species as an alternative and safe approach for the treatment of patients affected by cutaneous disorders, including non-healing wounds, has been recently reviewed [7,17]. Our data extend the spectrum of the mechanisms underlying the effects of specific probiotics on the re-epithelialization process and may further justify their use in the topical treatment of skin wounds.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely used probiotics are species from the genera Lactobacillus, Bifidobacterium, Saccharomyces, Enterococcus, Streptococcus, Pediococcus, Leuconostoc, Bacillus, Escherichia coli [3]. Oral administration of probiotics has shown to exert positive effects on intestinal and extra-intestinal disorders, including skin diseases [4][5][6][7]. Anyway, there is a growing body of research involving the use of a topical application of probiotics in dermatology with benefits in atopic dermatitis, acne, seborrheic dermatitis, and wound healing [4,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Yu et al (2019) evaluated whether the clinical data support the use of oral and topical probiotics for certain dermatologic diseases. The results showed that few clinical trials exist that evaluate the utility of probiotics for the prevention and treatment of dermatologic diseases, with the exception of AD.…”
Section: Meta-analysis Of the Probiotic Effectiveness On Skin Diseasesmentioning
confidence: 99%
“…1 Skin supports the growth of commensal bacteria, which, in turn, protects skin from pathogenic bacteria. [2][3][4] Human skin microbiota also produces modulators of immune system, such as short-chain fatty acids and metabolites of tyrosine or tryptophan; up regulates regulatory T lymphocytes, 5 and produces bacteriocin to out compete skin pathogens. 6 Human skin bacterial communities appear to be diverse.…”
Section: Introductionmentioning
confidence: 99%